“La justicia ambiental es para ti y para mí”: Translating Collective Struggles for Environmental and Energy Justice in Puerto Rico’s Jobos Bay Communities - Onís, Catalina M. de (Frontiers in Communication, 2021)
Rural, coastal communities in the Jobos Bay region of southeastern Puerto Rico confront disproportionate harms as an energy sacrifice zone. This space is constituted by imported fossil fuel dependency, economic and climate injustices, environmental racism, ecocide, US colonialism and imperialism, neoliberalism, and racial capitalism. In response, many grassroots actors mobilize against the toxic assault on their communities to push for alternatives beyond the suffocating status quo via apoyo mutuo [mutual support]. This survival work and movement building occur literally in “the outdoors” and in other intertwined multispecies environments, challenging narrow, oppressive colonial, and consumerist constructs that reduce “the outdoors” to recreation and thus erase the numerous ways that people labor in, honor, and defend places and spaces to lead good lives. Thus, critical examinations of communication and race/racism/racialization in and about this colonial US territory must grapple with the brutalities and pain caused by systemic and structural cruelties and translate how, where, and with whom self-determined and potentially liberatory environmental and energy justice advocacy takes shape to refuse a trauma-only narrative. Studying these embodied and emplaced efforts positions energy and power broadly construed, including in the form of collective action. This article centers on the collaborative energies of local grassroots actors and scholars who ideologically and politically align and who value working together toward anti-colonial praxis. To provide one example of how these collaborations can yield public-facing projects that contribute to struggles tied to the survival and well-being of the most impacted communities, this essay focuses on the creation of an environmental justice children’s book. This bilingual text documents and translates the pollution caused by a US-owned, coal-fired power plant and mobilizations to topple this corporate invader. The article concludes by reflecting on some of the difficulties and possibilities that emerged during multi-year coalitional relationships that inform and exceed the children’s book. To reject racist and colonial dominant assumptions and discourses about outdoor spaces as only privileged recreational areas or as a “blank slate” devoid of people and culture, this project narrates how grassroots organizers and scholars persist in continued study and struggle for power(ful) transformations in Jobos Bay and beyond.